Pharmacokinetic/Pharmacodynamic Analysis of Tedizolid Phosphate Compared to Linezolid for the Treatment of Infections Caused by Gram-Positive Bacteria - Alicia Rodríguez-Gascón; Amaia Aguirre-Quiñonero; María Angeles Solinís Aspiazu; Andrés Canut-Blasco (MDPI AG, 2021)
Tedizolid and linezolid have antibacterial activity against the most important acute bacterial skin and skin-structure infection (ABSSSIs) pathogens. The objective of this work was to apply PK/PD analysis to evaluate the probability of attaining the pharmacodynamic target of these antimicrobials based on the susceptibility patterns of different clinical isolates causing ABSSSI. Pharmacokinetic and microbiological data were obtained from the literature. PK/PD breakpoints, the probability of target attainment (PTA) and the cumulative fraction of response (CFR) were calculated by Monte Carlo simulation. PTA and CFR are indicative of treatment success. PK/PD breakpoints of tedizolid and linezolid were 0.5 and 1 mg/L, respectively. Probability of treatment success of tedizolid was very high (>90%) for most staphylococci strains, including MRSA and coagulase-negative staphylococci (CoNS). Only for methicillin- and linezolid-resistant S. aureus (MLRSA) and linezolid resistant (LR) CoNS strains was the CFR of tedizolid very low. Except for LR, daptomycin-non-susceptible (DNS), and vancomycin-resistant (VRE) E. faecium isolates, tedizolid also provided a high probability of treatment success for enterococci. The probability of treatment success of both antimicrobials for streptococci was always higher than 90%. In conclusion, for empiric treatment, PK/PD analysis has shown that tedizolid would be adequate for most staphylococci, enterococci, and streptococci, even those LR whose linezolid resistance is mediated by the cfr gene.